PENYULUHAN KRITERIA KELAYAKAN USAHA SARUNG TENUN GOYOR KABUPATEN PEMALANG DENGAN PERSPEKTIF KEUANGAN DAN PASAR SERTA PROSES PRODUKSI - Nasyita Vivi Amalia; Risal Ngizudin; Bekti Nugrahadi; Putty Alamanda; Nendi Setiawan (LPPM Universitas Al Muslim, 2024)
Woven fabrics as Indonesian cultural heritage needs to be preserved because they still have high value in the world community. One of them is the Goyor Woven Sarong which is a superior product for the creative economy of the Pemalang Regency. This community service activity aimed to determine the financial condition of the Goyor Woven Sarong industry, assess and develop product marketing strategies, and improve existing production systems. Counseling was carried out by providing appropriate material to real conditions in the Goyor Woven Sarong industry. These real conditions were obtained from observations by the team before the counseling was carried out. The delivery of material related to economic, market and production aspects needs to be emphasized considering increasingly tight business competition. The results of the implementation of this activity were the assessment and preparation of sales strategies for Goyor Pemalang Woven Sarongs. Thus, with this outreach activity it is hoped that sales will increase and be able to compete with other competitors.